DESAIN TEMATIK GAME EDUKASI UNTUK PENINGKATAN NILAI KEPEDULIAN DAN KETEKUNAN PADA KARAKTER ANAK DENGAN MODEL ASINKRON - Andy Pramono; Pujiyanto Pujiyanto; AAG Rai Arimbawa (JADECS (Journal of Art, Design, Art Education & Cultural Studies), 2019)
According to the Indonesian Ministry of Communication and Informatics data, at least 30 million children and adolescents in Indonesia are internet users, and digital media is currently the main choice of communication channels they use. One of the content that is the choice of users, especially children, is an interactive game. There is a strong assumption that interactive games can inhibit children's education, which makes children lazy to learn. The other side of character education is a target of the Indonesian government. Education about caring and perseverance is an important topic for children's character education. This article will discuss thematic learning media for raising children's awareness and perseverance which combines "game" and "learning" which are packaged with asynchronous models. Asynchronous was chosen because this character education still requires students to meet and discuss with teachers to find out the results of this education. This research is through a descriptive procedural research model, which outlines the steps that must be followed to produce a product. The data obtained in this design was taken by data observation, interview and documentation methods. Data observation method consists of visual data, library data and survey target audience. With the improvement of educational game design to increase children's care and perseverance, there will be an introduction, pattern and knowledge that can improve the character of children in life. This research can also be a guide for character education or one of the learning materials.